2023
DOI: 10.1161/jaha.122.028463
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Achieving Blood Pressure Targets and High Time in Therapeutic Range on Clinical Outcomes in Patients With Atrial Fibrillation Adherent to the Atrial Fibrillation Better Care Pathway: A Report From the COOL‐AF Registry

Abstract: Background We aimed to determine the effect of integrating Atrial Fibrillation Better Care pathway compliance in relation to achievement of systolic blood pressure (SBP) targets and good control of time in therapeutic range (TTR) on clinical outcomes in patients with atrial fibrillation. Methods and Results We prospectively enrolled patients with nonvalvular atrial fibrillation  from 27 hospitals in Thailand. All clinical outcomes were recorded. Main ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Indeed, the holistic approach has been associated with improved clinical outcomes, including lower mortality, stroke, and major bleeding. 23,24 A systematic review of 21 observational studies involved 96,448 patients showed that AF patients not OAC represent population at higher risk of bleeding. 5 Previous studies in AF patients with gastrointestinal bleeding who resume OAC had better subsequent ischemic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the holistic approach has been associated with improved clinical outcomes, including lower mortality, stroke, and major bleeding. 23,24 A systematic review of 21 observational studies involved 96,448 patients showed that AF patients not OAC represent population at higher risk of bleeding. 5 Previous studies in AF patients with gastrointestinal bleeding who resume OAC had better subsequent ischemic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the holistic approach has been associated with improved clinical outcomes, including lower mortality, stroke, and major bleeding. 23 24…”
Section: Discussionmentioning
confidence: 99%
“…This is clearly evident, for example, with respect to the importance of blood pressure (BP) control with optimal targets of 120–129 mmHg for systolic BP and <80 mmHg for diastolic BP to reduce the risk of adverse cardiovascular events, including stroke, bleeding, ICH, and hospitalisation from heart failure. 97 , 98 Hypertension burden is also closely related to the risk of other AF-associated complications such as dementia, 99 and visit-to-visit BP variability as a surrogate measure of the quality of BP control has been associated with worse outcomes in AF patients.…”
Section: Stroke Prevention With the C Component Of The Abc Pathwaymentioning
confidence: 99%
“…Indeed, adherence to the guideline-recommended Atrial fibrillation Better Care pathway can modify the natural history of AF, 8 24 even in highly complex AF patients. 25…”
mentioning
confidence: 99%